PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PEGADAIAN SYARIAH DI KOTA PEKANBARU - WIRDAYANI WAHAB (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2017)
The theme of the article is the banks and financial institutions. The study aims to determine the effect of service quality on customer satisfaction, and to know the difference. The study was conducted in the city of Pekanbaru. The sample was 100 respondents. The analytical method used is multiple linear regression analysis. The results showed: The quality of service has a positive effect on customer satisfaction.